Transitioning to No Poverty - Günther, Isabel; Lahoti, Rahul (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Transitioning to No Poverty is part of MDPI's new Open Access book series Transitioning to Sustainability. With this series, MDPI pursues environmentally and socially relevant research which contributes to efforts toward a sustainable world. Transitioning to Sustainability aims to add to the conversation about regional and global sustainable development according to the 17 SDGs. Set to be published in 2020/2021, the book series is intended to reach beyond disciplinary, even academic boundaries.